Report of the Joint Select Committee on the Boundary Question, with resolutions (Hawley & Faxon, State Printers, 1857)
Report to the General Assembly during May Session 1857. This is a followup on the report submitted by the Commissioners on the Western Boundary between Connecticut and New York. The joint committee attached a resolution to have the commissioners continue their work to resolve the boundary issue with New York.